Determination of maghrib and isya' times prayer by using Sky Quality Meter (SQM) and comparison data of moon programmer / Siti Husna Mohd Khirrudin - Mohd Khirrudin, Siti Husna (2010)
The study about how to determine the Islamic prayer times where it has been extensively investigated. The prayer times determination have been known that used traditional methods such as the human eye. Although the prayer time examined by the astronomer's but this project is to get closer to Allah and we are so blessed to be Muslim. In this project was presented 2 prayer times there are Maghrib and Isya's. In addition, shown the optical sky brightness at twilight measurement at Port Klang. The measurement was done using electronic device, SQM (Sky Quality Meter). Which can detect the brightness of sky and human eye. Based on the result the human eye still give the easiest way to predict the prayer time but SQM is best alternative device. Both of SQM and human eye measure the amount of perceived light at twilights which is coherent with the statement of the problem on visibility when there is no light. Most of data show that both measurements are ahead from official prayer times. This is because the measurements are made directly at the time rather than official prayer times which generate based on fix criterion.